Multidimensional Organizational Culture and Innovative Work Behavior in Indonesian Startup Organizations - Siti Nuroniah Magreth Febriola Haryanto; Pundani Eki Pratiwi (Universitas Ahmad Dahlan, 2026)
Innovation is critical for the sustainability of startup organizations operating in dynamic environments. Innovative work behavior (IWB) enables adaptation and competitiveness but is closely shaped by organizational culture. This study examined the association between organizational culture and IWB among 252 startup employees in Indonesia using a quantitative survey design. Organizational culture was assessed via the Organizational Culture Profile (innovation, outcome orientation, respect for people, attention to detail, and team orientation), while IWB was measured using Janssen’s (2000) scale. Multiple regression analysis indicated that organizational culture significantly predicted IWB (R² = .514, p < .001), explaining 51.4% of the variance, with innovation culture as the strongest predictor. Practically, startups should foster innovation-supportive climates by promoting psychological safety, structured idea-generation processes, and reward systems for experimentation. Strengthening team orientation and people-centered values may further enhance collaboration and knowledge sharing, thereby sustaining innovative performance in rapidly evolving startup ecosystems.